First visceral leishmaniasis focus in Argentina - Salomón, Oscar Daniel (2008)
An eight-year old boy from Posadas (27° 23′ S, 55° 54′ W) was diagnosed with visceral leishmaniasis (VL) during 2006. Lutzomyia longipalpis was discovered in the backyard of his house, while the spread of canine visceral leishmaniasis was confirmed in Posadas. This is the southernmost report of a VL transmission focus and the first in Argentina.